Transforming Islamic Religious Education through Local Wisdom and Cyber Ethics to Foster Global Harmony among Generation Z - Achmad Yusuf; Minhah Makhzuniyah; Aridlah Sendy Robikhah; Do'stnazar Ximmataliyev (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2026)
This study is motivated by Generation Z’s vulnerability to digital radicalization, religious disinformation, and global conflicts in cyberspace, thereby necessitating the reconstruction of a digital Islamic Religious Education (IRE) program that is technologically adaptive, rooted in local wisdom, and focused on strengthening cyber ethics. This research aims to formulate an integrative digital PAI model based on local wisdom and cyber ethics, as well as to analyze its effectiveness in building Generation Z’s multicultural awareness, digital responsibility, and reflective capacity as agents of peace. The study employed a qualitative design at SMKN 1 Purwosari through in-depth interviews with Islamic education experts, digital literacy activists, and students, supplemented by a systematic literature review. The findings indicate that, first, Generation Z exhibits specific vulnerabilities to digital radicalization stemming from generational characteristics, the digital ecosystem, and gaps in critical digital literacy. Second, the integration of local Islamic wisdom from the Nusantara region with cyber ethics in digital Islamic education is not only possible but also effective through an integrative model encompassing the pillars of digital moderation, communication ethics, information verification, digital responsibility, and digital harmony. Third, the implementation of this synergistic model has proven significant in enhancing cultural awareness, digital responsibility, and competencies as peace agents among Generation Z. This study confirms that the reconstruction of Islamic Education through an integrative approach is a strategic intervention that bridges normative Islamic values with contemporary digital challenges, while strengthening the contribution of Islamic education to fostering social harmony and global peace Keywords: Transforming; Islamic Religious Education; Local-Wisdom; Cyber-Ethics; Global Harmony